Higher Education and Sustainable Development Goals (SDG)—Potential Contribution of the Undergraduate Courses of the School of Social Sciences of the University of Évora - Chaleta, Elisa (2021)
In this work we analyzed the mapping of Sustainable Development Goals in the curricular units of the undergraduate courses of the School of Social Sciences at the University of Évora. Of a total of 449 curricular units, only 374 had students enrolled in 2020/2021. The data presented refer to the 187 course units that had Sustainable Development Goals in addition to SDG4 (Quality Education) assigned to all the course units. Considering the set of curricular units, the results showed that the most mentioned objectives were those related to Gender Equality (SDG 5), Reduced Inequalities (SDG 10), Decent Work and Economic Growth (SDG 8) and Peace, Justice and Strong Institutions (SDG 16). Regarding the differences between the departments, which are also distinct scientific areas, we have observed that the Departments of Economics and Management had more objectives related to labor and economic growth, while the other departments mentioned more objectives related to inequalities, gender or other.